Bioaccessibility and bioavailability changes of phenolic compounds in pumpkins (Cucurbita moschata): A review. (June 2022) - Yang, Zihong; BK, Amrit; Zhao, Wanrong; Shi, Linghong; Wu, Hanjing; Barrow, Colin; Dunshea, Frank; Suleria, Hafiz A.R.
Abstract: Pumpkin ( Cucurbita moschata ) is one of the well-known edible plants that contains several phytoconstituents, including polyphenols. The properties of medicinal values in pumpkin have been demonstrated, such as anti-diabetic, antioxidant, anti-carcinogenic, anti-inflammatory, hypolipidemic, and hypoglycemic. As functional compounds in pumpkins and the secondary metabolites in plants, the positive effects of polyphenols have been studied, including high antioxidant capacities and the mitigation potential of chronic diseases and certain cancers. This review is proposed to comprehensively investigate the interactions between phenolic compounds and pumpkin matrix constituents, including carbohydrates, proteins, lipids, minerals, vitamins, and other polyphenols, which will significantly impact the bioaccessibility and bioavailability of bioactive compounds in pumpkins, especially phenolics. Meanwhile, the effect on the nutritional properties of bioactive compounds has also been reported. Furthermore, this review includes the assessments for the food processing strategies to demonstrate the impact on phenolic intake capacity and changes in the content and properties of active compounds. Highlights: Phenolic compounds with high health properties are widely present in pumpkin. Phenolics may change as they travel through the gastrointestinal tract. Phenolics interact with macromolecules and micromolecules in pumpkin matrix. Matrix interactions affect the bioaccessibility and bioavailability of phenolics. The effects of processing strategies on food properties were critically discussed.